2011
DOI: 10.12693/aphyspola.120.234
|View full text |Cite
|
Sign up to set email alerts
|

Binding Energy of the Hydrogenic Impurity in CdTe/ZnTe Spherical Quantum Dot

Abstract: Binding energy of a hydrogenic impurity located at the center of the CdTe/ZnTe spherical quantum dot has been calculated under the effective mass approximation by solving Schrödinger equation analytically. Eigen energies are expressed in terms of the Whittaker function and Coulomb wave function. The results show that impurity binding energy strongly depends on QD size if it is around one effective Bohr radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is observed that the binding energy increases with decreasing dot radius and it reaches the maximum value for a critical dot radius and then rapidly decreases in all the cases. It is because the contribution of connement is dominant for smaller dot radii making the electron unbound with the spread of the wave function through the barrier [24]. The dotted points refer the results obtained by Stojanovi£ and Kosti£ [24] who calculated the hydrogenic impurity in CdTe/ZnTe spherical quantum dot analytically.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…It is observed that the binding energy increases with decreasing dot radius and it reaches the maximum value for a critical dot radius and then rapidly decreases in all the cases. It is because the contribution of connement is dominant for smaller dot radii making the electron unbound with the spread of the wave function through the barrier [24]. The dotted points refer the results obtained by Stojanovi£ and Kosti£ [24] who calculated the hydrogenic impurity in CdTe/ZnTe spherical quantum dot analytically.…”
Section: Resultsmentioning
confidence: 82%
“…It is because the contribution of connement is dominant for smaller dot radii making the electron unbound with the spread of the wave function through the barrier [24]. The dotted points refer the results obtained by Stojanovi£ and Kosti£ [24] who calculated the hydrogenic impurity in CdTe/ZnTe spherical quantum dot analytically. Our results are in good agreement with their analytical results.…”
Section: Resultsmentioning
confidence: 82%